Differences in school boards with hired and elected superintendents: a first look. (1st October 2016) - Ford, Michael R.; Ihrke, Douglas M.
Abstract: In this article, we use original survey data collected from Florida school board members to determine if the perceived benefits of an appointed local government executive apply to the school board context. Though we observe a performance advantage for school districts with appointed superintendents, the advantage appears to be a function of school district size and demographics rather than government form. Similarly, observed differences in board governance dynamics in districts with elected as opposed to appointed superintendents appear to be a function of factors other than government form. Finally, we find that board members are more likely to delegate day-to-day financial management duties to appointed superintendents. Overall, we conclude that the government form literature does not necessarily translate to special purpose governments. The results are of interest to scholars of local government, education administration, and group dynamics.